Identification of Nucleolus-Associated Chromatin Domains Reveals a Role for the Nucleolus in 3D Organization of the A. thaliana Genome - Pontvianne, Frédéric; Carpentier, Marie-Christine; Durut, Nathalie; Pavlištová, Veronika; Jaške, Karin; Schořová, Šárka; Parrinello, Hugues; Rohmer, Marine; Pikaard, Craig S; Fojtová, Miloslava; Fajkus, Jiří; Sáez-Vásquez, Julio (Cell reports, 2016)
The nucleolus is the site of rRNA gene transcription, rRNA processing, and ribosome biogenesis. However, the nucleolus also plays additional roles in the cell. We isolated nucleoli using fluorescence-activated cell sorting (FACS) and identified nucleolus-associated chromatin domains (NADs) by deep sequencing, comparing wild-type plants and null mutants for the nucleolar protein NUCLEOLIN 1 (NUC1). NADs are primarily genomic regions with heterochromatic signatures and include transposable elements (TEs), sub-telomeric regions, and mostly inactive protein-coding genes. However, NADs also include active rRNA genes and the entire short arm of chromosome 4 adjacent to them. In nuc1 null mutants, which alter rRNA gene expression and overall nucleolar structure, NADs are altered, telomere association with the nucleolus is decreased, and telomeres become shorter. Collectively, our studies reveal roles for NUC1 and the nucleolus in the spatial organization of chromosomes as well as telomere maintenance.
Keywords: RNA ribozomální; ribozomální DNA; fosfoproteiny; DNA, Ribosomal; nucleolus; nucleolus-associated chromatin domains; Genome, Plant; nuclear architecture; telomery; proteiny vázající RNA; Cell Nucleolus; Transcription, Genetic; nukleolin; Phosphoproteins; Telomere; heterochromatin; Heterochromatin; Nucleolin; RNA, Ribosomal; genetická transkripce; telomere; RNA-Binding Proteins; exprese genu; Arabidopsis; buněčné jadérko; genom rostlinný; Gene Expression